2019
DOI: 10.3390/agronomy9110771
|View full text |Cite
|
Sign up to set email alerts
|

Steeping of Biofortified Orange Maize Genotypes for Ogi Production Modifies Pasting Properties and Carotenoid Stability

Abstract: Biofortified orange maize open-pollinated varieties and hybrids with higher provitamin A carotenoids (pVACs) have been released in sub-Saharan Africa and will be introduced throughout the local food systems. This study assessed the impact of steeping, a traditional processing method, on retention of carotenoids and starch pasting properties of porridges made from select biofortified maize genotypes. Steeping had a modest effect (<9% loss) on total carotenoid stability during relatively shorter steeping peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…The result shows that carotenoids in biofortified PVA maize will reduce with an increase in the processing steps, especially the unit operations, which involve heat, extended exposure to light, and physical friction. This depleting impact of processing on PVA in maize was also confirmed by Ortiz et al (80), where the impact of steeping (fermentation) was probed in maize genotypes. It was also observed that both processing and genotypes influence carotenoid retention.…”
Section: Carotenoid True Retention Profilesupporting
confidence: 71%
“…The result shows that carotenoids in biofortified PVA maize will reduce with an increase in the processing steps, especially the unit operations, which involve heat, extended exposure to light, and physical friction. This depleting impact of processing on PVA in maize was also confirmed by Ortiz et al (80), where the impact of steeping (fermentation) was probed in maize genotypes. It was also observed that both processing and genotypes influence carotenoid retention.…”
Section: Carotenoid True Retention Profilesupporting
confidence: 71%
“…They play an essential role in the applications of starch in the food industry and other industries (Berski et al, 2011). The variation in the pasting properties of the Striga-resistant yellow-orange maize hybrids might be attributed to their differential starch composition, as earlier suggested by Ortiz et al (2019). It is known that starch containing more branched amylopectin achieves high peak viscosities due to its propensity to absorb and retain more water (Gayral et al, 2015).…”
Section: Pasting Properties Of Striga-resistant Yellow-orange Maize Hmentioning
confidence: 97%